2012
DOI: 10.1093/ejcts/ezs144
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of transthoracic ultrasound for the detection of pleural adhesions

Abstract: Transthoracic ultrasound is an effective method for predicting pleural adhesions before thoracic surgery in experienced hands. Its safety, feasibility and low cost make it a useful method for the planning of minimally invasive surgical interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 14 publications
1
48
0
Order By: Relevance
“…Cassanelli et al [29] already showed that ultrasound is able to detect pleural adhesions. Future studies might investigate whether patients with more peripheral destruction in panlobular or paraseptal emphysema and adjacent pleural adhesions are at higher risk of developing pneumothorax than patients with a more centrilobular emphysema.…”
Section: Discussionmentioning
confidence: 99%
“…Cassanelli et al [29] already showed that ultrasound is able to detect pleural adhesions. Future studies might investigate whether patients with more peripheral destruction in panlobular or paraseptal emphysema and adjacent pleural adhesions are at higher risk of developing pneumothorax than patients with a more centrilobular emphysema.…”
Section: Discussionmentioning
confidence: 99%
“…If lung sliding is present, there are no pleural adhesions in the intended surgical site. If no lung sliding is present, adhesions should be suspected and the incision should be performed elsewhere [239]. Lung recruitment following positive end-expiratory pressure can be assessed with LUS [158, 178].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, pleural-parenchymal adhesions are not easily predictable [10]. Although a recent study has used an ultrasound approach to predict the presence of adhesions before lung operations, directing the surgeon towards an open or video-assisted approach, the confirmation of partial or complete obliteration of the pleural space can only be obtained at the time of thoracotomy [11]. The lysis of pleural parenchymal adhesions with limited extension is generally performed with gentle blunt manual or instrumental dissection or by monopolar or bipolar electrocautery [12].…”
Section: Discussionmentioning
confidence: 99%